Digital Literacy based Instruction in Teaching English in EFL Classroom - Jusmawati, Jusmawati; Jafar, Muhammad Basri; Salija, Kisman (Har Press Indonesia, 2023)
This study aims to determine the teachers perceive on digital literacy in Indonesia English As A Foreign Language Classroom, to know the implemented of digital literacy in teaching English in Indonesia English As a Foreign Language Classroom, and how digital literacy impact on students’ performance in Indonesia EFL classroom. This research adopts case study, where the research subject are two teachers all the English teachers and 23 students which consisted 15 females and 8 males. in this research of the result shows both of the teachers have a high perception on digital literacy in Indonesia EFL Classroom, the researcher finds there are 3 steps of implementing digital literacy in EFL classroom such as plan, action, and reflection, and the impact of digital literacy in students’ English performance shows a positive result on students’ English performance.